2021
DOI: 10.1002/ccd.29663
|View full text |Cite
|
Sign up to set email alerts
|

Revascularisation strategies in patients with significant left main coronary disease during the COVID‐19 pandemic

Abstract: Background There are limited data on the impact of the COVID‐19 pandemic on left main (LM) coronary revascularisation activity, choice of revascularisation strategy, and post‐procedural outcomes. Methods All patients with LM disease (≥50% stenosis) undergoing coronary revascularisation in England between January 1, 2017 and August 19, 2020 were included ( n = 22,235), stratified by time‐period (pre‐COVID: 01/01/2017–29/2/2020; COVID: 1/3/2020–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…We analyzed all patients who underwent PCI for stable angina in England and Wales between January 1, 2006, to December 31, 2017, in the BCIS database. Based on our previously published work, CHiP was defined as any procedure with at least one clinical high‐risk feature, such as (age ≥ 80, previous history of CABG or chronic renal failure, or severely impaired left ventricular function) and/or one procedural (anatomical) high‐risk factor such as (left main PCI, severe vessel calcification, chronic total occlusion PCI, or the need of LV support) 5,17,18 . All CHiP procedures were then stratified by sex into male or female groups.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed all patients who underwent PCI for stable angina in England and Wales between January 1, 2006, to December 31, 2017, in the BCIS database. Based on our previously published work, CHiP was defined as any procedure with at least one clinical high‐risk feature, such as (age ≥ 80, previous history of CABG or chronic renal failure, or severely impaired left ventricular function) and/or one procedural (anatomical) high‐risk factor such as (left main PCI, severe vessel calcification, chronic total occlusion PCI, or the need of LV support) 5,17,18 . All CHiP procedures were then stratified by sex into male or female groups.…”
Section: Methodsmentioning
confidence: 99%
“…There was also evidence of change in choice of procedural strategy. Amongst patients with left main coronary artery stenosis in the UK, there was observation of both a reduction in revascularisation procedures and greater use of PCI over coronary artery bypass grafting 36 .…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, a study from England showed a 48.8% reduction in left main revascularization during the pandemic compared with previous years, with a shift towards PCI as the preferred strategy to minimize patients’ exposure to the hospital environment and preserve ICU beds for COVID-19 patients. Post-procedural mortality remained the same in the both pre-COVID-19 and COVID-19 periods, suggesting that quality of outcomes was maintained during the pandemic [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients awaiting structural heart disease (SHD) interventions constitute a particularly challenging group, as many have conditions that might be life threatening if the intervention is inappropriately delayed [ 25 •, 26 – 29 ]. Studies have shown a decline in surgical and transcatheter aortic valve procedures during the pandemic with potential increase in mortality [ 24 , 25 •, 26 – 29 ] (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%